Preoperative hypoglycemia in a patient receiving insulin detemir. - Olson, R; Bethel, M; Lien, L (2009)
The insulin regimen of a Type 2 diabetic presenting for surgery had been changed recently from a 70/30 mixture of insulin aspart protamine and aspart to insulin detemir and insulin glulisine. Preoperative instructions were to take the usual dose of basal, but none of the short-acting insulin. On the morning of surgery, the patient's blood glucose was low and remained so despite i.v. dextrose administration. A review of the basal insulin dose revealed that it had been inappropriately increased to control elevated postprandial glucose. Doses of basal insulin in excess of basal requirements will cause hypoglycemia in the fasting state.